The housing cycle in emerging Middle Eastern economies and its macroeconomic policy implications - Beidas, S. (Samya); Lian, Weicheng; Maseeh, Ashwaq (IMF working paper, 2009)
This paper examines housing finance and housing price dynamics in selected emerging Middle Eastern economies over the past two decades. It finds that (i) mortgage markets have experienced rapid development, which has led to lower private per capita consumer spending volatility this decade; (ii) a downward price correction occurred in the housing market after 2007, which appears to have bottomed out; (iii) the rental market appears to be largely determined by region-specific economic fundamentals-a youthful working-age population and wealth variables; and (iv) a segregation between self-owned house and rental price dynamics exists in this region, rendering the former more sensitive to the business cycle.